2023
DOI: 10.1039/d2nj06241k
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide targeted “turn-on” fluorescence sensing enabled by a diselenide based quinoline probe and its in vitro anticancer activity in cancer cells

Abstract: First organoselenium-based quinoline probe was successfully synthesized and characterized by common spectroscopic techniques. The probe was found to be selective and sensitive for superoxide detection over other reactive oxygen species...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A significantly high IC 50 value (65.21 mM) indicated that the probe had better biocompatibility with normal cells (MDCK) and that it would be a compelling drug for the treatment of lung cancer cells. 98…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A significantly high IC 50 value (65.21 mM) indicated that the probe had better biocompatibility with normal cells (MDCK) and that it would be a compelling drug for the treatment of lung cancer cells. 98…”
mentioning
confidence: 99%
“…The reaction mechanism of the probe with O 2 À (grey: weak fluorescence signal; green: emitted yellow-green fluorescence), and microscopic photographs in MKDC cells in control group (A) and treated with the probe at concentrations of 1 mM (B). Reproduced with permission 98. Copyright 2023, Royal Society of Chemistry.…”
mentioning
confidence: 99%